2017
DOI: 10.1097/md.0000000000007489
|View full text |Cite
|
Sign up to set email alerts
|

VASA mRNA (DDX4) detection is more specific than immunohistochemistry using poly- or monoclonal antibodies for germ cells in the male urogenital tract

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The germline and TGCT markers that we used in this study are considered to be widely accepted “gold standards” both at mRNA and protein levels [ 31 33 ]. However, the sole use of correlation of expression of the PIWI/piRNA pathway with these markers still leaves room for alternative explanations of our results (for instance, that PIWI/piRNA pathway may function to a different extent in both germ cells and GCNIS cells in testis tissues adjacent to TGCTs).…”
Section: Discussionmentioning
confidence: 99%
“…The germline and TGCT markers that we used in this study are considered to be widely accepted “gold standards” both at mRNA and protein levels [ 31 33 ]. However, the sole use of correlation of expression of the PIWI/piRNA pathway with these markers still leaves room for alternative explanations of our results (for instance, that PIWI/piRNA pathway may function to a different extent in both germ cells and GCNIS cells in testis tissues adjacent to TGCTs).…”
Section: Discussionmentioning
confidence: 99%
“…These cells, which appear to be T1-prospermatogonia, migrate to the seminiferous tubules and produce T2 pre-spermatogonia during the first post-natal week. These cells fill the basement membrane and begin the spermatogenesis pathway throughout the post-pubertal life 35 , 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Abbasi et al reported that in immunohistochemistry analysis of THY1 (A conserved marker of SSCs of bovine, rodents, and primates) positive cells were all positive for DDX4 ( 37 ). Several investigations have analyzed DDX4 expression in normal human and mice ( 24 , 38 ). In the present study, comparison of two different abnormal cases with different levels of tissue disruption was done which showed that the expression of spermatogonia had decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Next studies demonstrated that DDX4. (A member of the DEAD (Asp-Glu-Ala-Asp) box family proteins) gene encodes an ATP-dependent RNA helicase which regulates the translation of at least two mRNAs during germ cell development, nanos and gurken ( 24 ). The DDX4 gene has a conserved sequence in invertebrates and vertebrates such as C. elegans, planarian, xenopus, zebrafish, frog, mouse, rat, cat, pig, rhesus macaques, goat, chicken, and human.…”
Section: Introductionmentioning
confidence: 99%